Breach with Intent: A Risk Analysis of Deliberate Security Breaches in the Seafood Supply Chain - Forbes, David; Alexander, Paul (Springer, 2015)
Global seafood supply chains are amongst the most complex of any, typically requiring short shelf life products to be transported long distance with stringent temperature and quality control. These requirements and large-scale outsourcing,wide-scale use of intermediaries, and often multiple transformation processes create opportunities for product quality failures, particularly at participant handover points, conversions, and transport mode changes. Failures include bothdegradation of the physical condition of seafood and damaged trust perceptions about its integrity and identity. These occur not only by accident, but sometimes willfully. Quality failures and negative market perceptions have the potential to do great damage in seafood supply chains with significant financial impact and even collapse of whole markets.Much work has already been contributed on unintentional quality problems in seafood supply chains, so in this chapter we provide a review of the seafood supply chain with a focus on intentional security breaches. We examine the susceptibility to security degradation of the components of the supply chain and the forms it takes. We highlight existing mechanisms used to identify and counter these events, and we posit technologies and strategies that can be employed to minimise them.